2020
DOI: 10.21203/rs.3.rs-110130/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Validation of preimplantation genetic tests for aneuploidy (PGT-A) with DNA from spent culture media (SCM): concordance assessment and implication

Abstract: Background: Spent culture medium (SCM) as a source of DNA for preimplantation genetic tests aneuploidy (PGT-A) has been widely discussed. Methods: Seventy-five blastocysts donated for research provided a unique possibility in which multiple specimens, including trophectoderm (TE) biopsy, SCM, and paired corresponding whole blastocyst (WB) specimens from the same blastocyst source, could be utilized for the purpose of this preclinical validation.Results: To conduct a validation ploidy concordance assessment, we… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…PGT-A by trophectoderm biopsy or whole embryo and SCM showed a consistency rate between 78.2% and 100% 18–23. However, other studies reported a consistency rate between 32.2% and 56.3% 24 25…”
Section: Introductionmentioning
confidence: 87%
“…PGT-A by trophectoderm biopsy or whole embryo and SCM showed a consistency rate between 78.2% and 100% 18–23. However, other studies reported a consistency rate between 32.2% and 56.3% 24 25…”
Section: Introductionmentioning
confidence: 87%
“…All 42 embryos provided informative results, but only 85.7% had ploidy concordance across sample types (66.7% full and 19.0% partial). Yin et al, 2021 worked with 75 thawed day-5/6 embryos, where TE biopsy had already been performed and that were cultured for 24 h. Although the informativity rate was 78.7%, the ploidy concordance rate was 89.8% (32.2% full and 57.6% partial). Ho et al, 2018, Huang et al, 2019, Shitara et al, 2021and Chen et al, 2021a, also compared some of the SBM, not only with TE, but also with whole embryos (33, 48, 16 and 256, respectively), obtaining high informativity rates for the SBM (97.6%, 92.3%, 95% and 96.6%, respectively) but disparate ploidy concordance rates: 45.5%, 93.7%, 93.8% and 78.1%, respectively (Table 2).…”
Section: Embryonic Cfdna Analysis For Nipgt-a: Concordance Studiesmentioning
confidence: 99%
“…The benefit of such procedure has not been confirmed (Ho et al, 2018). Other manipulations that were performed include vitrification (Xu et al, 2016;Huang et al, 2019;Jiao et al, 2019;Zhang et al, 2019b;Chen et al, 2020;Yin et al, 2021;Shitara et al, 2021;Li et al, 2021), collapsing of the embryo and/or biopsy before media collection (Feichtinger et al, 2017;Kuznyetsov et al, 2018;Huang et al, 2019;Jiao et al, 2019;Zhang et al, 2019b;Chen et al, 2020;Li et al, 2021;Sialakouma et al, 2021). Moreover, there are publications where a completely non-invasive protocol is performed achieving ploidy concordance rates with TE biopsy as high as 84% (Rubio et al, 2019;.…”
Section: ) Is Assisted Hatching (Ah) or Previous Vitrification Needed?mentioning
confidence: 99%
“…Among these research contents, the abnormal cleavage pattern of embryos is an important one. Studies have found that abnormal cleavage directly affects the genome of a single cell in human embryos, resulting in chromosome loss and mosaicism, thereby reducing embryonic developmental potential, resulting in embryonic developmental arrest and significantly reduced blastocyst formation rates [16][17][18].…”
Section: Introductionmentioning
confidence: 99%